Legal Protection of Workers’ Rights in Employment Relationships in Indonesia: A Normative Analysis and Implementation - Idris. Idris; Muhammad Dhobit Azhary Lubis (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2026)
The enactment of Law Number 13 of 2003 concerning Manpower was motivated by the disadvantaged position of workers in employment placement and industrial relations systems that accentuated unequal positions and conflicting interests, rendering previous regulations inadequate for contemporary demands. This study aims to analyze the implementation of legal protection for workers’ rights within employment relations in Indonesia, and to identify barriers and corresponding remedial efforts. Employing a normative juridical approach with qualitative-deductive analysis, this research reveals that despite juridical equality between workers and employers under Pancasila, the 1945 Constitution, and Law No. 13/2003, practical asymmetries in power relations persist, undermining the fulfillment of workers’ fundamental rights. Key obstacles include regulatory loopholes, non-egalitarian legal culture, weak enforcement oversight, and companies’ financial constraints. Addressing these issues requires state intervention through regulatory refinement, strengthened labor supervision, and dispute resolution mechanisms that prioritize substantive justice over mere contractual freedom. This study contributes to mapping the dichotomy between protective norms and field implementation, while offering actionable policy recommendations.